Questioning the substance use among the attendants of substance dependence panel organized in Gülhane Military Medical Faculty - Kayır, Hakan; İpekdal, İlker; Evrensel, Alper; Uzbay, İ. Tayfun (Journal of Dependence, 2000)
Object: Substance dependence is a growing problem especially in developing countries. It was aimed at questioning substance abuse status and knowledge of attendants and commenting the results via a questionnaire in the panel about substance dependence has been arranged in Gülhane Military Medical Academy (GATA) in 1998.Method: Questionnaire forms have been given to each attendant. Personal information, substance abuse status and thoughts about substance dependence have been questioned. 344 of 362 questionnaire sheet (95%) accepted for study.Results: Analysis showed that smoker rate is 39%, alcohol abuser rate is 40% and illicit drug user rate is 2.3% among the responders. Affection of using another substance increases in responders using only cigarette or alcohol. Initial age for smoking is 15.7 in males and 18.12 in females; initial age for alcohol is 17 in males and 19.8 in females. 71% of responders are aware of severity of substance dependence. Large amount of responders (87%) agree that people and family must be educated for substances to reduce the rates of dependence.Discussion: It is found that smoking and alcohol using rates of attendants are really high. Also found that using substances with another is more common, and friendship connection is the main cause for beginning to use substances. Epidemiological researches which contain more and different people will help us to find more effective ways to reduce the substance dependence.
Keywords: Alcohol; Cigarette; Substance Dependence